GLOBAL CIVILIZATION MADRASAH BASED ON MOSQUES: ISTIQLAL JAKARTA MADRASAH STUDY - Taufiqurrahman, Mochammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Mosques are places of worship for Muslims. However, the function of mosques is not limited to just being a place of worship, but also as a center of learning, especially in religious education. During the time of Rasulullah SAW, mosques had various functions such as places of worship (prayers), centers for education, teaching, justice, economic empowerment of the people, information centers, military training and government. This research aims to: Describe the role of the Istiqlal Mosque as the main center in the development of Islamic education. Analyzing the Istiqlal Madrasah education program which integrates the values of Islamic education and science and technology. The research results show that Madrasah Istiqlal Jakarta functions as a mosque-based madrasah that supports global civilization. This madrasah is not only a religious educational institution, but also a center for character and intellectual development for the young generation of Muslims who are ready to contribute to the development of a just and prosperous global civilization. Istiqlal Madrasah has several unique characteristics that differentiate it from traditional madrasas, namely: Integrated Curriculum, Innovative Learning Approach, Islamic Character Development, and Openness to the World.